Structural characterization and DNA-binding properties of Sm(III) complex with ofloxacin using spectroscopic methods. Issue 2 (2009) - Chen Chen, Changyun Changyun; Chen Chen, Kai Kai; Long Long, Qi Qi; Ma Ma, Meihua Meihua; Ding Ding, Fei Fei
Abstract : A novel complex Sm(III) complex with ofloxacin was synthesized and characterized on the basis of elemental analyses, molar conductivities, IR spectra, thermal analysis (TG-DSC), 1 H-NMR spectra. Then, spectrometric titration, ethdium bromide displacement experiments by UV spectroscopy, ionic influence, viscosity measurements and Circular Dichroism (CD) spectroscopic measurements were conducted to characterize the interaction between the complex and CT-DNA. Results obtained indicate that the complex bound with CT-DNA via an intercalation mechanism. The binding constants and binding sites number of the Sm(III) complex with CT-DNA were 1.80×10 5 l·mol −1 and 1, respectively.